Post-COVID-19 Malaysian parents’ views on children’s vaccination: subjective norms analysis - Abd Rahman, Noor Amira Syazwani; Ju, Soon-Yew; Razali, Jamal Rizal; Hamdan, Nur Hazirah; Ridzuan, Mohd Rozaimy; Kong, Lai-Kuan (International Journal of Evaluation and Research in Education (IJERE), 2024)
Vaccinating children is a critical life-saving measure that ensures herd immunity and saves numerous lives. However, the rising trend of parental refusal to vaccinate poses a significant threat to disease containment within societies. Amid the widespread COVID-19 pandemic in Malaysia, this study examines how subjective standards impact parents’ vaccination intentions and behaviors. Lockdowns and travel restrictions during the pandemic caused a decline in vaccination rates due to missed appointments for children’s vaccinations. Even post-pandemic, some parents persist in refusing vaccination for their children. Conducting an online survey and employing quantitative, the study collected data from parents with children aged 1 day to 15 years old. Analyzing the data through IBM SPSS and employing SmartPLS 4.0.9.5 software, specifically using partial least squares-structural equation modeling (PLS-SEM), revealed significant insights. The findings indicate that parents’ willingness to vaccinate their children significantly predicts their actual vaccination behavior. Moreover, social norms positively influence parental vaccination intentions. The study highlights the mediating role of vaccination intention between social norms and actual vaccination behavior among parents. Overall, this empirical research strongly supports the theory of planned behavior (TPB) model, emphasizing the importance of targeting social norms to foster vaccination behavior and elevate vaccination rates.